Hypoxia-induced transcriptional stress is mediated by ROS-induced R-loops - Ma, Tiffany S; Worth, Katja R; Maher, Conor; Ng, Natalie; Beghè, Chiara; Gromak, Natalia; Rose, Anna M; Hammond, Ester M (Nucleic acids research, 2023)
Abstract Hypoxia is a common feature of solid tumors and is associated with poor patient prognosis, therapy resistance and metastasis. Radiobiological hypoxia (<0.1% O2) is one of the few physiologically relevant stresses that activates both the replication stress/DNA damage response and the unfolded protein response. Recently, we found that hypoxia also leads to the robust accumulation of R-loops, which led us to question here both the mechanism and consequence of hypoxia-induced R-loops. Interestingly, we found that the mechanism of R-loop accumulation in hypoxia is dependent on non-DNA damaging levels of reactive oxygen species. We show that hypoxia-induced R-loops play a critical role in the transcriptional stress response, evidenced by the repression of ribosomal RNA synthesis and the translocation of nucleolin from the nucleolus into the nucleoplasm. Upon depletion of R-loops, we observed a rescue of both rRNA transcription and nucleolin translocation in hypoxia. Mechanistically, R-loops accumulate on the rDNA in hypoxia and promote the deposition of heterochromatic H3K9me2 which leads to the inhibition of Pol I-mediated transcription of rRNA. These data highlight a novel mechanistic insight into the hypoxia-induced transcriptional stress response through the ROS–R-loop–H3K9me2 axis. Overall, this study highlights the contribution of transcriptional stress to hypoxia-mediated tumorigenesis. Graphical Abstract Graphical Abstract